Investigation of the Analytical F14C Bone Background Value at SUERC. Issue 5 (11th August 2017) - Dunbar, E; Naysmith, P; Cook, G T; Scott, E M; Xu, S; Tripney, B G
Abstract: The SUERC Radiocarbon Laboratory employs a one-step "background subtraction" method when calculating 14 C ages. An interglacial wood (VIRI Sample K) is employed as the non-bone organic background standard, while a mammoth bone (LQH12) from Latton Quarry is used as the bone background standard. Results over several years demonstrate that the bone background is consistently around a factor of two higher and more variable than the wood background. As a result, the uncertainty on routine bone measurements is higher than for other sample types. This study investigates the factors that may contribute to the difference in F 14 C values and the higher variability. Preparations of collagen using modified Longin or ultrafiltration methods show no significant difference, nor does eliminating the collagen dissolution step. Two bone samples of known infinite age with respect to radiocarbon are compared and again no significant difference is observed. Finally, the quantity and age of the organic matter in the water used during the pretreatment is investigated and it is shown that there is insufficient organic matter in the reverse osmosis water to influence background values significantly. The attention is now on determining if incomplete demineralization could lead to contaminants being retained by the phosphate in the hydroxyapatite.